2021
DOI: 10.22214/ijraset.2021.38609
|View full text |Cite
|
Sign up to set email alerts
|

Fake News Detection Using Various Machine Learning Algorithms

Abstract: Reports have been around for a long time and have a track record of producing accurate results. The fast development of online media stages has increased the adverse consequence of bits of gossip; it accordingly gets essential to early identify them. Numerous techniques have been acquainted with distinguishing reports utilizing the substance or the social setting of information. In any case, most existing strategies overlook or don't investigate viably the engendering example of information in online media, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…In paper [3], the researchers believe that many fake news stories contain many facts, and conversely, many true news stories contain a lot of false information. Therefore, the researchers evaluated the performance of four machine learning algorithms that work on detecting fake news with the help of natural language processing methods, and after training, the results were as shown in the In research papers [6] and [7], the focus was on machine learning algorithms such as Passive Aggressive classifier and Logistic regression that were applied in a set of algorithms to determine the best algorithm for detecting fake news. In the paper [6], four machine learning algorithms were used, including the Naïve Bayes algorithm, Support vector machine classification, Logistic regression, Passive Aggressive classifier, and some natural language processing techniques such as a bag of words and TD-IDF.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In paper [3], the researchers believe that many fake news stories contain many facts, and conversely, many true news stories contain a lot of false information. Therefore, the researchers evaluated the performance of four machine learning algorithms that work on detecting fake news with the help of natural language processing methods, and after training, the results were as shown in the In research papers [6] and [7], the focus was on machine learning algorithms such as Passive Aggressive classifier and Logistic regression that were applied in a set of algorithms to determine the best algorithm for detecting fake news. In the paper [6], four machine learning algorithms were used, including the Naïve Bayes algorithm, Support vector machine classification, Logistic regression, Passive Aggressive classifier, and some natural language processing techniques such as a bag of words and TD-IDF.…”
Section: Related Workmentioning
confidence: 99%
“…The practical application results showed that the Passive Aggressive classifier gave the highest accuracy rate of 99.5%. In the paper [7], the researchers sought to determine whether the idea of using artificial intelligence to solve the problem of fake news is valid or not by creating a website that can help users verify fake news. Three machine learning algorithms were used, namely Logistic Regression, Naïve Bayes, and Random Forest, as well as some natural language processing techniques, and the results are shown in the table below: In the paper [8] three models were utilized, including RoBERTa, a pre-trained language model from the BERT family, Bi-LSTM, a deep learning algorithm, and Passive Aggressive Classifier, a machine learning technique.…”
Section: Related Workmentioning
confidence: 99%
“…Data is collected either by web scraping [1], a website can be used to scrap fake news and true news and various classifiers like SVM [1] [7,13], random forests [1,3,4,8] or the combination of both like in [13] where SVM-RF produces a higher accuracy can be used. Kaggle and other websites can be used to collect datasets but, in this project, web scraping is done.…”
Section: Theoreticalmentioning
confidence: 99%
“…Graph Transformer network (GTN) [2] can also be used but the limitation here is emotions and sentiment analysis has not been taken into consideration which vastly effects the results. TF-IDF and count vectorizer [3,5,7,8] is used for feature extraction and a weighing scheme [7] that assigns weights to the features involved can be implemented for feature extraction. A BERT based deep learning approach [10] is implemented and python libraries are used for the same.…”
Section: Theoreticalmentioning
confidence: 99%
See 1 more Smart Citation